2016
DOI: 10.1007/978-3-319-39955-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Paired Associative Stimulation with Brain-Computer Interfaces: A New Paradigm for Stroke Rehabilitation

Abstract: In conventional rehabilitation therapy to help persons with stroke recover movement, there is no objective way to evaluate each patient's motor imagery. Thus, patients may receive rewarding feedback even when they are not complying with the task instructions to imagine specific movements. Paired associative stimulation (PAS) uses brain-computer interface (BCI) technology to evaluate movement imagery in real-time, and use this information to control feedback presented to the patient. We introduce this approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…We also found that older patients had difficulty with the bar feedback when classification was incorrect, because it was hard to associate the corresponding movement with the feedback. Some recent work has validated VR technology within the context of MI BCIs for stroke rehabilitation (Luu et al, 2015 ; Soekadar et al, 2015 ; Remsik et al, 2016 ; Sabathiel et al, 2016 ). Therefore, a newer version of the recoveriX system uses a virtual avatar, and the patient sees the left and right hands in a first-person perspective (Sabathiel et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that older patients had difficulty with the bar feedback when classification was incorrect, because it was hard to associate the corresponding movement with the feedback. Some recent work has validated VR technology within the context of MI BCIs for stroke rehabilitation (Luu et al, 2015 ; Soekadar et al, 2015 ; Remsik et al, 2016 ; Sabathiel et al, 2016 ). Therefore, a newer version of the recoveriX system uses a virtual avatar, and the patient sees the left and right hands in a first-person perspective (Sabathiel et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since closed-loop feedback that is effectively paired with the desired mental activity is a critical facet of any feedback system (Neuper and Allison, 2014 ), the “paired stimulation” (PS) made possible through motor-imagery BCI research could improve therapy outcomes. Recent research from several groups has supported this hypothesis (Ang et al, 2011 ; Pichiorri et al, 2011 , 2015 ; Ortner et al, 2012 ; Luu et al, 2015 ; Sburlea et al, 2015 ; Soekadar et al, 2015 ; Remsik et al, 2016 ; Sabathiel et al, 2016 ; Serrano et al, 2017 ). Furthermore it is known that a closed feedback loop increases the users performance (Wolpaw et al, 2002 ).…”
Section: Introductionmentioning
confidence: 95%
“…It is then just a natural step to try and incorporate available models of synaptic plasticity to underpin the desired adaptive behavior of neuroprosthetic or BCI systems; the involved strategies for closed-loop, real-time hybrid system, and the associated development of "neuromorphic" chips, also have potential to possibly augment PAS, endowing them with adaptive capabilities. In the PAS domain, such options just begin to be considered (Royter et al, 2016;Sabathiel et al, 2016); in the following, to provide a hint at available methodologies to make progress towards closed-loop, adaptive PAS systems, we first briefly touch upon the present status of implementable synaptic plasticity models, and next…”
Section: Section 4: Prospects In Neuromorphic Circuitsmentioning
confidence: 99%
“…By adding the MI BCI into the control loop, rewarding feedback such as avatar movement and FES activation is only possible when the patient performs the correct MI. This BCI-based feedback is much more tightly coupled to each patient's MI than conventional means, which should increase the functional improvement from therapy training (Remsik et al, 2016 ; Sabathiel et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%